PENGEMBANGAN BURUNG HANTU (TYTO ALBA) SEBAGAI PENGENDALI HAMA TIKUS DI DESA BABAHAN DAN SENGANAN, PENEBEL, TABANAN, BALI - Sukmawati, N. M. S.; Siti, N.W.; Candraasih K, N.N. (Buletin Udayana Mengabdi; Vol 16 No 1 (2017), 2018)
Society service to purpose the effectivity of Tyto alba on rats pest control in Babahan and Senganan village, Penebel, Tabanan has conducted for 5 months. The methods used were : 1) participatory coordination and communication with the member of subak and Umawali group, 2) training in Demak, 3) conservation and 4) put artificial nest (rubuha) in rice field area. From this activity, there are 12 heads of Tyto alba have been conservated. In 2016, the population increased to be 22 heads with 17 units of artificial nest (rubuha). Some of rubuha have been reside by wild tyto alba. The Umawali reported that Tyto alba could reduced pest rats about 70%. The barn owls Tyto alba can consume 3-5 heads of rat per night and can fly in 12 km of circle. Based on the result of this activity, it concluded that Tyto alba is very effective as a control of rats pest.